Improvement of N-Acetylcysteine Loaded in PLGA Nanoparticles by Nanoprecipitation Method. (5th July 2018) - Lancheros, Ruth; Guerrero, Carlos A.; Godoy-Silva, Rubén D.
Abstract : N-Acetylcysteine (NAC) is a hydrophilic compound with a low bioavailability. It has been used as an effective antioxidant agent. This research seeks to enhance the entrapment of NAC in PLGA nanoparticles for drug delivery systems. The nanoparticles were made using the nanoprecipitation method and changing the following parameters: the solvent/nonsolvent nature, its viscosity, pH, NAC addition to the nonsolvent, the polymer concentration and molecular weight, and NAC concentration in the solvent. The results showed that an increase in the nonsolvent viscosity produces NAC concentration in the solvent, and the nonsolvent rises its entrapment in the nanoparticles. Nanoparticles with 235.5 ± 11.4 nm size with an entrapment efficiency of 0.4 ± 0.04% and a specific load of 3.14 ± 0.33% were obtained. The results suggest that besides efficiently entrapping hydrophobic compounds, the nanoprecipitation method also has a high potential as an alternative entrapment method for hydrophilic compounds as well. However, its use in the pharmaceutical industry, as a proper specific load vehicle, still depends on the improvement of the load capacity.